Proces oblikovanja družine v Sloveniji - Černič Istenič, Majda (Družboslovne razprave, 1998)
Nowadays women in Slovenia postpone first births similarly as women in other European countries. In order to explain this phenomenon the relationship between education, working, housing and partnership careers and probability of having a first birth is examined. The basic hypothesis is that the entry into a partnership union (irrespective of its status), end of regular attendance of school, entry into the first job, solved housing problem at the time of birth of the first child, the establishment of one's own household and characteristics of the socialization process have greater impact on the rate of entry into motherhood than the entry into first marriage and the levelof education. The analysis is based on data from "Quality of life in Slovenia - retrospective study 1974-1994". A parametric regression modelling with time-varying covariates has been applied in analysing event histories of 306 women born between 1985-1976. Results show that the rate of entry into motherhood is most strongly influenced by the entry into a partnership union, end of regular attendance of schooling and solved housing problem at the time of birth of the first child. This findings are briefly compared with similar international research findings.
Keywords: sociologija družine; družina; family; kvaliteta življenja; materinstvo; načrtovanje življenja; načrtovanje družine; Slovenia; Slovenija